COMPARATIVE STUDY BETWEEN PERIOSTIN AND OSTEOCALCIN AS BIOMARKERS FOR OSTEOPOROSIS AND FRACTURE RISK IN EGYPTIAN POSTMENOPAUSAL WOMEN - MOHAMED, ALAA SALAM; KHALIFA, ASHRAF ISMAIL; ABOTALEB, ASHRAF ABDEL-MONEAM; ELDESOKY, NOHA ABDEL-RAHMAN (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: This study aimed to compare between periostin and osteocalcin as biomarkers in Egyptian postmenopausal women with osteoporosis and to explore their possible relationship with fracture risk. Methods: This study included 90 postmenopausal females recruited from Al-Hussein University Hospital, Cairo, Egypt; divided into three groups; 35 postmenopausal osteoporotic females with low fracture risk (group I), 35 postmenopausal osteoporotic females with high fracture risk (group II), and 20 apparently healthy controls. Serum periostin, osteocalcin, and estrogen were measured by Enzyme Linked Immunosorbent Assay (ELISA). Fracture risk assessment was calculated. Alkaline phosphatase (ALP), total and ionized calcium, Aspartate transaminase (AST), and Alanine transaminase (ALT) were measured spectrophotometrically. Results: The diagnostic performance of periostin for discriminating high fracture risk from low fracture risk groups showed the specificity of (68.6 %) and sensitivity of (100 %), while for osteocalcin the specificity was (51.4 %) and the sensitivity was (68.6 %) respectively. Moreover, the multi Receiver Operating Characteristics (multi-ROC) curve for periostin and osteocalcin together revealed improved specificity and sensitivity of (100 %) each. Conclusion: Periostin was superior to osteocalcin in discriminating high fracture risk from low fracture risk postmenopausal osteoporotic groups. Moreover, dual use of both markers gave the highest discriminative power between low and high fracture risk groups with 100 % specificity and sensitivity.